Language Heightened. Issue 2 (25th November 2022) - Abts, Devon
Abstract : Poets and calligraphers are united in their appreciation for the beauty of words. Yet whereas many poets compose according to principles of sound, the calligrapher is guided above all by the sense of sight. This essay seeks to elucidate the hermeneutical dynamics at play in contemporary calligraphic renderings of poetic texts composed for oral recitation, using the work and interpretive legacy of Victorian poet Gerard Manley Hopkins as a test-case. After briefly introducing my theme, I turn to consider Hopkins's theory and practice of aural composition, drawing on specific poems to illuminate his mastery of acoustic depth. I go on to examine three transcriptions of his work by three contemporary calligraphic artists, focusing on key interpretive choices each scribe makes when translating Hopkins's aural art into a visual form. At each stage of my investigation, I demonstrate how both the poet and his interpreters invite recipients of their artwork to a deeper appreciation for the wonder of language in ordinary circumstances.